Household decision-making and its association with intimate partner violence: Examining differences in men's and women's perceptions in Uganda. (August 2019) - Zegenhagen, Sasha; Ranganathan, Meghna; Buller, Ana Maria
Abstract: Introduction: A vast body of evidence identifies intimate partner violence (IPV) as a public health and human rights issue with detrimental health consequences. The exploration of household decision-making, as an indicator of women's empowerment, and its association with IPV has so far yielded mixed results, mostly due to measurement issues. Given the sizeable investment in women's empowerment initiatives, and their potential to improve women's health, it is important to elucidate the relationship between household decision-making and IPV. Methods: We conducted a secondary analysis of the 2011 Uganda Demographic and Health Survey (DHS) data to explore the relationship between women's household decision-making and experience of physical IPV. The dependent variable in our analysis was past year physical violence and it was constructed using men's reported perpetration of partner violence (men's questionnaire). Six independent variables were included – one each for men and women's perspectives on who usually makes decisions about the following domains: 1) how money earned is spent, 2) health care, and 3) large household purchases. We ran a probit model, controlling for variables featured in our theoretical framework. Results: The association between household decision-making and women's likelihood of experiencing IPV depended on the decision-making domain and on who reported it. Women's reporting on decision-making did not predict their experience of IPV, whereas men's reporting on two decision-making domains (large household purchases and expenditure of husband's earnings) predicted likelihood of women experiencing IPV. Joint decision-making and women's decisions alone in both of these domains were associated with a lower probability of IPV compared to husband's making the decisions alone, where husband's reported decision-making. Conclusion: This study demonstrates that men's views on coupled dynamics should be included in program design and evaluation to provide a more holistic picture of the ecological framework and risk and protective factors of IPV. Highlights: Women's reporting on decision-making did not predict their experience of IPV. Men's decision-making on large purchases and their earnings predict IPV risk. Decision-making measurement should consider decision-making domains. Collaborative household decision-making may predict lower probability of IPV. Men's views on couple dynamics should be included in program design and evaluation